Penerapan Model Problem Based Instruction untuk Meningkatkan Hasil Belajar Siswa - Khoirun Nisa; Moch Shohib (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
Quality education is able to produce a generation that is competitive in accordance with the times. One of many aspects determining the quality of education is the level of teacher professionalism in delivering subject matter, especially mathematics material which is known to be difficult and makes students bored in the learning process. This study uses a classroom action research method with the research subjects of the fifth grade students of MIS Tarbiyatul Mubtadiin Labruk Lor Lumajang, with 31 students, researchers and teachers. The data collection technique used is triangulation. The results showed that the fifth grade mathematics educator (teacher) of MIS Tarbiyatul Mubtadiin Labruk Lor Lumajang used a problem-based instruction model to increase student activity and learning outcomes in mathematics subjects.